A prospective study of social competence in survivors of pediatric brain and solid tumors. Issue 9 (20th March 2022) - Albee, May; Allende, Santiago; Cosgrove, Victoria; Hocking, Matthew C.
Abstract: Background/objectives: Survivors of pediatric brain tumors are at increased risk for difficulties with social competence, including poor social information processing (SIP) and peer relationships. Improved survival rates heighten the need to better understand these challenges and if they are specific to survivors of pediatric brain tumors versus survivors of other childhood cancers. Methods: Fifty‐one survivors of pediatric brain tumors and 34 survivors of pediatric solid tumors completed evaluations of SIP and peer relationship quality within six months of completing treatment and one year later. Caregivers completed a measure of social skills. Linear mixed models evaluated differences between survivors of pediatric brain and solid tumors on SIP and social skills and how indices of SIP were associated with peer relationships over time. Results: The two groups did not differ on indices of SIP or social skills over time. A three‐way interaction between measures of SIP, group, and time predicted peer relationships. Survivors of pediatric solid tumors showed a positive association between baseline social skills and theory of mind and peer relationships over time, whereas survivors of pediatric brain tumors showed an inverse association between baseline social skills and theory of mind and peer relationships over time. Conclusion: Findings revealed unanticipated associations between baseline SIP and social skills and peer relationships over time among survivors of pediatric brain tumors. Additional research is needed to elucidate the factors most influential on peer relationships in this group to inform interventions.